Unconventional Brochure - Yasmin Wita Al Hadida (IC-ITECHS, 2020)
Brochure is a common marketing tool used for advertising products or services. Brochure makes delivering information better than searching for the information over the internet using search engines. Nowadays, with the rapid development of printing technology, everyone can print brochures easily. The problem that often happened is that rapid usage of brochure in which it is usually discarded immediately after reading. If it happens continuously, it will cause a big environmental issue. Due to the issue, graphic designers are expected to have creative solutions for reducing the waste of brochure by making creative, reusable design, yet decreasing discarding the brochures by its users. A solution which accommodate the human needs, saving resources and the nature and environment sustainability should be created. Unconventional brochure is a brochure that has an unusual shape. The purpose of it is to make people feel they have something valuable from the brochure, so they will keep it as long as possible. The limitation of the content that conventional brochures can carry is generally quite troublesome because there are a lot of information needs to be omitted. Therefore, QR code (Quick Response Codes) and AR (Augmented Reality) brochure has real visualization and can give more realistic approach to the brochure content. Thus, we can use QR Code or AR technology as a way to support sustainable development.